The Problem of Acquaintance of the Defense with the Materials Submitted to the Court Pursuant to Art. 108 of the Criminal Procedure Code - Nikolai V. Azarenok (Сибирское юридическое обозрение)
On the basis of the existing order of submission of materials to the court by an investigator needed to decide on remand in respect of criminal prosecuted person, identify problems familiarize the defense with these documents at trial. The Author studies norms of the Criminal Procedure Code of the Russian Federation, decisions of the Constitutional Court of the Russian Federation and the Supreme Court of the Russian Federation, as well as interviews with practitioners in this aspect. As a result, a conceptual approach to solvingthe identified problem is proposed.